Визначення сторінок дискусій віртуальної спільноти для інформаційного впливу - Гумінський, Руслан; Пелещишин, Андрій (Видавництво Львівської політехніки, 2017)
The article describes the procedure, which will determine the key (critical) elements (gravity centers) of the virtual community according to the elements number and the links between these elements for further impact.
Keywords: віртуальні спільноти; інформаційний вплив; об’єкт впливу